Measuring the English vocabulary acquisition of Japanese learners - Yoshie Ishikawa; Ayano Otaki; Hiromu Okamura; Tomohiko Shirahata (Universitas Syiah Kuala, 2024)
The measurable vocabulary knowledge of Japanese learners of English (JLEs) has yet to be fully investigated. This study, therefore, attempts a detailed investigation of JLEs' vocabulary knowledge to clarify the relationship between the frequency of words and their difficulty level and to identify the factors that affect the difficulty of vocabulary learning. We tested 192 university-level JLEs on 1,035 verbs, requesting that they choose a correct Japanese translation.  The average number of correct answers for each verb was compared with its frequency ranking. Moreover, the characteristics of verbs that received high and low percentages of correct answers were examined. The three major findings were as follows. First, the average number of correct answers was 751.97 (72.65% of the verbs investigated). Second, the average number of correct answers decreased as the frequency of the verb decreased. However, this tendency diminished beyond the 4,000-word level. Finally, not a few low-frequency verbs garnered a high percentage of correct answers; these were verbs that included affixes or were English loanwords that were possibly known to JLEs. However, other low-frequency verbs received a low percentage of correct answers because they had abstract or multiple meanings and lacked clues that could facilitate an understanding of the word's meaning. We concluded that these were the main factors affecting the degree of difficulty in learning each vocabulary item. Regarding this study's pedagogical implications, efficient use should be made of English-based loanwords and affixes, and university-level JLEs should intentionally learn low-frequency words.